Cannabinoids in the Treatment of Epilepsy: Current Status and Future Prospects - Morano A (Dove Medical Press, 2020)
Alessandra Morano,1 Martina Fanella,1 Mariarita Albini,1 Pierangelo Cifelli,2,3 Eleonora Palma,2 Anna Teresa Giallonardo,1 Carlo Di Bonaventura1 1Epilepsy Unit, Department of Human Neurosciences, “Sapienza” University of Rome, Rome, Italy; 2Department of Physiology and Pharmacology, Pasteur Institute-Cenci Bolognetti Foundation, University of Rome Sapienza, Rome, Italy; 3IRCCS “Neuromed”, Pozzilli, IS, ItalyCorrespondence: Carlo Di BonaventuraEpilepsy Unit, Department of Human Neurosciences, “Sapienza” University of Rome, P.le A. Moro, 5, Rome 00185, ItalyEmail c_dibonaventura@yahoo.itAbstract: Cannabidiol (CBD) is one of the prominent phytocannabinoids found in Cannabis sativa, differentiating from Δ9-tetrahydrocannabinol (THC) for its non-intoxicating profile and its antianxiety/antipsychotic effects. CBD is a multi-target drug whose anti-convulsant properties are supposed to be independent of endocannabinoid receptor CB1 and might be related to several underlying mechanisms, such as antagonism on the orphan GPR55 receptor, regulation of adenosine tone, activation of 5HT1A receptors and modulation of calcium intracellular levels. CBD is a lipophilic compound with low oral bioavailability (6%) due to poor intestinal absorption and high first-pass metabolism. Its exposure parameters are greatly influenced by feeding status (ie, high fat-containing meals). It is mainly metabolized by cytochrome P 450 (CYP) 3A4 and 2C19, which it strongly inhibits. A proprietary formulation of highly purified, plant-derived CBD has been recently licensed as an adjunctive treatment for Dravet syndrome (DS) and Lennox-Gastaut syndrome (LGS), while it is being currently investigated in tuberous sclerosis complex. The regulatory agencies’ approval was granted based on four pivotal double-blind, placebo-controlled, randomized clinical trials (RCTs) on overall 154 DS patients and 396 LGS ones, receiving CBD 10 or 20 mg/kg/day BID as active treatment. The primary endpoint (reduction in monthly seizure frequency) was met by both CBD doses. Most patients reported adverse events (AEs), generally from mild to moderate and transient, which mainly consisted of somnolence, sedation, decreased appetite, diarrhea and elevation in aminotransferase levels, the last being documented only in subjects on concomitant valproate therapy. The interaction between CBD and clobazam, likely due to CYP2C19 inhibition, might contribute to some AEs, especially somnolence, but also to CBD clinical effectiveness. Cannabidivarin (CBDV), the propyl analogue of CBD, showed anti-convulsant properties in pre-clinical studies, but a plant-derived, purified proprietary formulation of CBDV recently failed the Phase II RCT in patients with uncontrolled focal seizures.Keywords: cannabidiol, cannabidivarin, phytocannabinoids, epileptic encephalopathies, tuberous sclerosis complex, drug-resistance